Mastering core IDRAW 7 - Altman, Rick (BPB Publications , New Delhi, 1997)
"Mastering CorelDRAW 7 is the comprehensive guide to the latest version of Corel's popular graphics program. Written by acclaimed CorelDRAW expert Rick Altman, this new edition of a long-standing best-seller covers every feature, function, and added capability, in a design both inviting to the beginner and practical for the experienced user. The easy-to-follow presentation shows you how to use CorelDRAW to create any image you want. Turn here for complete coverage."--Jacket
O level